Autobiographical Accounts of War Experiences. An Outline for the Analysis of Topically Focused Autobiographical Texts – Using the Example of the "Robert Rasmus" Account in Studs Terkel’s Book, "The Good War" - Schütze, Fritz (Qualitative Sociology Review, 2014)
The paper demonstrates both: firstly, a research strategy for the social science analysis of autobiographical narrative interviews, and, secondly, a research strategy for the social science use of published oral history and/or autobiographical materials. It is an attempt to demonstrate a text-oriented procedure of biography analysis in the social sciences, especially – sociology. This allows the empirically grounded generation both of general theoretical concepts for socio-biographical processes, and of conceptual provisions for the uniqueness of the features and dynamics of biographical and historical single cases, their situations, and phases. The paper deals with the analysis of autobiographical accounts of war experiences and it shows the general mechanisms of collective, social, and biographical processes, on the one hand, and the uniqueness of historical, situational, and biographical developments, on the other, coexist during wars in an especially ironical, tragic, elating, depressive, dangerous, hurting, deadly combination.